Gender medicine: its historical roots. Issue 1138 (29th May 2020) - Lippi, Donatella; Bianucci, Raffaella; Donell, Simon
Abstract: Gender medicine as a subject began with Bernadine Healy's 1991 article 'The Yentl Syndrome' which showed that women had worse outcomes following heart attacks since their symptoms are different from men. Since then gender-specific clinical research protocols have been progressively included so that evidence for guidelines can be better informed such that women are then less disadvantaged and care become more personalised. This paper traces back the historical roots of gender bias in medicine in Western culture, which is reflected in the pictorial arts and writings of each historical period, beginning with Hippocrates. It describes the changes that have led to attempts at improving the place of women, and the treatments of disease, on an equal footing with men, precipitated by Healy's paper.